Studies on plasma assisted molecular beam epitaxial growth of GaN-based multilayer heterostructures on Si for photodetector application - Zheng, Yi (2019)
III-Nitride materials have gathered enormous attention and undergone fast development, due to superior properties such as wide band gap, high stability, high electron motilities, high break down voltage and sensitivity to ultraviolet light. GaN ultraviolet (UV) detector can be used in fire detecting, missile’s seeker, combustion process monitoring and other monitoring systems, which require UV detection in harsh environments. Tunability of band gap and the possibility of formation of heterostructures with group III-nitride materials allow the design of complex structures to detect both UV and infra-red (IR) spectral regimes (multi band) on a single chip. By growing AlGaN/GaN multiple quantum well layers, IR detector can also be obtained, which means IR and UV detector can be achieved using the same material. GaN based UV/IR dual band photodetectors can be grown on sapphire, Si or SiC substrate, but sapphire and SiC substrates are more expensive than Si. Moreover, development of such a technology on Si allows lower cost and opens the prospect of integration of III-nitride with Si technology. UV/IR dual band detectors grown on sapphire substrates without any optical filter has also been reported. However, growth of such photodetectors on Si (111) substrate is challenging due to large difference in thermal and lattice mismatch between Si substrate and GaN, which leads to built-in strain and cracking. In this work, plasma assisted molecular beam epitaxy (PA-MBE) is used to grow dual band photodetector heterostructures on Si substrate as well as MOCVD grown AlN/Si templates. In this thesis, prior to the growth of complex multiple layer photodetector structures, GaN and AlGaN growth on Si substrate as well as AlN/Si template are optimized. The effect of the AlN layer on the GaN surface morphology and crystal quality is studied. AlN layer failed to block Ga diffusion because of columnar structure or grain boundary formed, due to N-rich AlN growth in MBE, which could act as a path for Ga diffusion into Si substrate and dissolve in Si forming Ga-Si alloy. The Ga-Si alloy would float on Ga droplets during the growth and end up in microcrystal. Separate two-step growth of AlN and GaN together makes GaN surface smooth without microcrystals. Smooth GaN/AlN grown on Si (111) by PA-MBE without microcrystals is achieved with the RMS roughness ~0.4 nm. Si doping concentration in GaN is found non-linear to Si cell temperature at higher doping levels. Prior to AlN buffer layer growth, amorphous SiNx formed on Si surface can also be used as buffer layer to achieve smooth GaN on Si substrate. Importantly, it has been confirmed that SiNx layer acts as a blocking layer for Ga/Si diffusion across the AlN layer. Based on GaN growth, AlGaN growth in Ga-rich condition was optimized in a similar way. AlGaN layer with 30% Al-composition optimized on Si (111) substrate, AlN template deposited in-house by MOCVD and commercial AlN template showed comparable surface morphology. Si doping studies of AlGaN with Al-composition of 30% are conducted on both 4-inch Si (111) substrate and MOCVD grown AlN/Si template. The highest Si doping of 2×1020 cm3 is achieved with RMS surface roughness less than 1 nm. Crack-free wafers with total GaN or AlGaN epilayer thickness up to 1.4 µm have been achieved. Multiple layer structures for UV photodetector application are successfully grown on Si substrate and AlN/Si template. Different mesas are designed for the UV photodetectors to the study the effect of device dimensions on photoresponsivity. Low dark current density in the order of 103 A/m2 is observed. Photocurrent measurements under different applied bias (1 to 3 V) and wavelength of light are performed. Square photodetector showed high responsivity of 1 A/W at 3 V bias while the interdigitated detector with similar sensing area showed even higher responsivity of 5.7 A/W. In the interdigitated design, larger detecting area and shorter lateral electrodes-gap help to improve the photoresponsivity. AlGaN/GaN based multiple layer structure for UV/IR dual band photodetector application is successfully grown on AlN/Si template. Interdigitated photodetector fabricated on epilayer grown on AlN/Si template show a low dark current density of 7 × 103 A/m2 at 15 V applied bias in room temperature. Clear UV response of 0.01 A/W from the fabricated photodetectors has been demonstrated. The near-IR optical photoresponse observed is at 4.52 µm up to about 50 K.